Astrogliosis in aging and Parkinson's disease dementia: a new clinical study with 11C-BU99008 PET. Issue 5 (18th August 2022) - Mohamed, Mohamed A; Zeng, Zhou; Gennaro, Marta; Lao-Kaim, Nicholas P; Myers, Jim F M; Calsolaro, Valeria; Femminella, Grazia Daniela; Tyacke, Robin J; Martin-Bastida, Antonio; Gunn, Roger N; Nutt, David J; Edison, Paul; et al.
Abstract: The role of astrogliosis in the pathology of brain aging and neurodegenerative diseases has recently drawn great attention. Imidazoline-2 binding sites represent a possible target to map the distribution of reactive astrocytes. In this study, we use 11 C-BU99008, an imidazoline-2 binding sites-specific PET radioligand, to image reactive astrocytes in vivo in healthy controls and patients with established Parkinson's disease dementia. Eighteen healthy controls (age: 45–78 years) and six patients with Parkinson's disease dementia (age: 64–77 years) had one 11 C-BU99008 PET-CT scan with arterial input function. All subjects underwent one 3 T MRI brain scan to facilitate the analysis of the PET data and to capture individual cerebral atrophy. Regional 11 C-BU99008 volumes of distribution were calculated for each subject by the two-tissue compartmental modelling. Positive correlations between 11 C-BU99008 volumes of distribution values and age were found for all tested regions across the brain within healthy controls ( P  < 0.05); furthermore, multiple regression indicated that aging affects 11 C-BU99008 volumes of distribution values in a region-specific manner. Independent samples t -test indicated that there was no significant group difference in 11 C-BU99008 volumes of distribution values between Parkinson's disease dementia ( n  = 6; mean age = 71.97 ± 4.66 years) and older healthy controls ( n  = 9; mean age = 71.90 ± 5.51 years). Our data set shows that astrogliosis is common with aging in a region-specific manner. However, in this set-up, 11 C-BU99008 PET cannot differentiate patients with Parkinson's disease dementia from healthy controls of similar age. Abstract : This is an imaging study in Parkinson's disease dementia with 11 C-BU99008 PET (experimental radioligand developed to assess astrocytic distribution in the living brain). Mohamed M. and Zeng Z et al . report that astrogliosis is common with aging in a region-specific manner. Here, 11 C-BU99008 PET does not differentiate these patients from healthy controls. Graphical Abstract: Graphical abstract